Examining technology orientation constructs: A validation study - Ajibike, W. A.; Adeleke, A. Q.; Fazeeda, Mohamad; M. N.M., Nawi; T.D., Moshood (GITO Verlag, P, 2020)
This study validates technology orientation (TO) constructs in the Malaysian construction industry context. Using a well-structured online-administered questionnaire, the data was collected from one hundred and eighty-five representatives of Grade 7 (G7) construction firms comprises of top or middle management level who are involved in the day-to-day running of the firm as well as taking strategic decisions about how the firms are been run like CEO, Executive Director, Managing Director, Construction Managers, and Project Managers). The data was analyzed using Smart-PLS 3 software. Results of this analysis revealed that all the technology orientation’s dimensions namely, technology capability, top management capability, learning (commitment to learning), and unlearning (commitment to change) were highly applicable. Acceptable level of internal consistency, reliability, discriminant validity, and convergent validity for each of the constructs of the technology orientation was established. Based on the outcome of the analysis, it is therefore recommended that the TO instrument are suitable for measuring all the constructs of TO to study how Malaysian construction firms can combine their capabilities to build the assets of the organization and allow them to be utilized in a wellorganized and efficient way.